1996
DOI: 10.1677/erc.0.0030243
|View full text |Cite
|
Sign up to set email alerts
|

History of LHRH agonist and combination therapy in prostate cancer

Abstract: An LHRH agonist was first administered to a prostate cancer patient 16

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 22 publications
1
26
0
1
Order By: Relevance
“…Short-term administration of cyproterone acetate resulted in a substantial reduction of testicular androgen production. Cyproterone acetate is an antagonist of androgens acting at the receptor (reviewed in Labrie et al, 1996) and has also been shown to reduce serum testosterone concentrations both in rats and in men (Knuth et al, 1984;Gonzalvo et al, 1993), as well as in hyperandrogenic states in women (Grunwald et al, 1994;Grigoriou et al, 1996;Grisaru et al, 1996). The latter effect is due to the action of cyproterone acetate (particularly at high doses such as those used in our study) acting as a progestagen at the hypothalamus to inhibit the release of GnRH (Couzinet et al, 1986).…”
Section: Discussionmentioning
confidence: 49%
“…Short-term administration of cyproterone acetate resulted in a substantial reduction of testicular androgen production. Cyproterone acetate is an antagonist of androgens acting at the receptor (reviewed in Labrie et al, 1996) and has also been shown to reduce serum testosterone concentrations both in rats and in men (Knuth et al, 1984;Gonzalvo et al, 1993), as well as in hyperandrogenic states in women (Grunwald et al, 1994;Grigoriou et al, 1996;Grisaru et al, 1996). The latter effect is due to the action of cyproterone acetate (particularly at high doses such as those used in our study) acting as a progestagen at the hypothalamus to inhibit the release of GnRH (Couzinet et al, 1986).…”
Section: Discussionmentioning
confidence: 49%
“…Today, prostate cancer can be diagnosed at the clinically localized stage in more than 95% of cases Despite the progress achieved in the treatment of advanced or metastatic prostate cancer using LHRH agonists [35,56] and especially with combined androgen blockade [36,37,39,40,[45][46][47][48], it is well recognized that the only possibility of a significant reduction in prostate cancer mortality is the treatment of localized disease [57]. It is reasonable to suggest that the observed decrease in deaths from prostate cancer is due to earlier diagnosis with serum PSA [58,59] and transrectal ultrasound of the prostate [60] coupled with improved treatment of localized disease by surgery, radiotherapy, brachytherapy, and endocrine therapy [57,[61][62][63][64].…”
Section: Combined Androgen Blockade In Advanced Diseasementioning
confidence: 99%
“…In the prostate epithelium 3 -HSD expression was colocalized with 17 -HSD type V in normal conditions. 3 -HSD was found in human hyperplastic prostates suggesting the capacity of the human prostate for local androgen production, that increase the hypertrophic potential of the organ [80,81]. Hepatic 3 -HSD expression is presumed to be important in the metabolism and inactivation of steroids.…”
Section: -H S D I M M U N O H I S T O C H E M I S T R Y I S a L S O Umentioning
confidence: 99%